Patern of Worker Fatigue for Standing Position of Shopkeeper - Santoso, Gempur; Prihono (UNIPA PRESS, 2021)
Work fatigue is a health and safety problemthat can be a trigger factor for accidents atwork. The purpose of this study was to analyzethe standing work position with work fatigueon the sales clerk (shop assistant) in the TradeShop, Sidoarjo. This type of research usesanalytic observational research, with a samplesize of 21 employees, with the technique oftaking through questionnaires and interviewsfor each employee in September, 2020. Thelevel of fatigue is analyzed using a percentage,with categories: 1 - ≤ 25 (Not Tired) , > 25 - ≤50 (Less Tired),> 50 - ≤ 75 (Tired), and> 75 - ≤ 100 (Very Tired). The results showed thatthe level of fatigue felt by a sales assistant(shop assistant) with a standing work positionwas in the